Ion‐Specific Assembly of Strong, Tough, and Stiff Biofibers. Issue 51 (4th November 2019) - Mittal, Nitesh; Benselfelt, Tobias; Ansari, Farhan; Gordeyeva, Korneliya; Roth, Stephan V.; Wågberg, Lars; Söderberg, L. Daniel
Abstract: Designing engineering materials with high stiffness and high toughness is challenging as stiff materials tend to be brittle. Many biological materials realize this objective through multiscale (i.e., atomic‐ to macroscale) mechanisms that are extremely difficult to replicate in synthetic materials. Inspired from the architecture of such biological structures, we here present flow‐assisted organization and assembly of renewable native cellulose nanofibrils (CNFs), which yields highly anisotropic biofibers characterized by a unique combination of high strength (1010 MPa), high toughness (62 MJ m −3 ) and high stiffness (57 GPa). We observed that properties of the fibers are primarily governed by specific ion characteristics such as hydration enthalpy and polarizability. A fundamental facet of this study is thus to elucidate the role of specific anion binding following the Hofmeister series on the mechanical properties of wet fibrillar networks, and link this to the differences in properties of dry nanostructured fibers. This knowledge is useful for rational design of nanomaterials and is critical for validation of specific ion effect theories. The bioinspired assembly demonstrated here is relevant example for designing high‐performance materials with absolute structural control. Abstract : A hydrodynamics‐based approach for the organization and assembly of fibrillar building blocks into hierarchical macrostructures with multiscale control over the nanostructure leads to exceptional mechanical properties. For the first time, structure–property relationships are understood depending on specific ion effects for wet and dry nanofibrillar systems.